DISTRIBUTION AND ORGANIZATION OF THE TERRITORY OF PRE-HISPANIC HUAROCHIRI DURING LATE PERIOD. ESSAY: A VIEW FROM WORSHIP OF CAMAC AND “HÉROES MÍTICOS– PAQARINAS O FUNDADORES”. - Bravo Meza, Bradymir Bitzen (2015)
In pre-Hispanic Huarochirí of later periods (Late Intermediate and Late Horizon) the sense of membership of an ethnic identity of the Andean peoples is based on the cult of the hero camac mythical-paqarina or founder (mythical character whose exploits, achievements and projects hydraulic and / or agricultural transform the old times and order in which they were immersed in a new community where the community acquires a greater power in the Andean territory, so generations of community members is considered a descendant of the mythical hero ) the presence of cult Huallallo Carhuincho Apu Apu Pariaqaqa and then, becomes in this context the conciliator gear and justifier of the ancient relationships and conflicts of ancestral communities, which are imposed on the territory by the efforts of prehistoric peoples they expand their influence and / or control of territory. Since this approach during the Late Intermediate provinces of Huarochiri and Yauyos not have belonged to the same ethnic identity called Yauyu, but rather find divided into a set of community groups attached to an identity based on the cult of the mythical hero camac founder -paqarina or strengthened by the conflicts of the Andean peoples, but which in turn are establishing ancestral links - but plausible to transgress - Pariaqaqa cult (the new time and order in which is immersed in the central area of the Sierra de lime). During this period the role of females is camac huacas or transcendental, because through them the Apu huaca and can inherit the ancient times and order in which they are subjected communities through strategic marriage alliances. During the Late Horizon, sponsored by the Inca state apparatus hegemonizes Pariaqaqa pan-regional cult, and puts Yauyu as stewards of their worship. Although the prehistoric peoples of Huarochiri, share the same pan-regional cult with the province of Yauyos, they maintain their allegiance to a common identity based on hero worship their camac paqarina or mythical founder. During the Tawantinsuyu complexity of the organization of worship under the Inca rule Huarochirí reveals a pattern of territorial distribution of the archipelagos of worship (cults camac or foreign huacas inserted in local cults) as control strategy type.